Global macroeconomic cooperation and the exchange rate system - José Antonio Ocampo Gaviria (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper looks at historical and current frameworks to manage macroeconomic linkages among economies. It considers first the evolving nature of global payments imbalances. It then focuses on the mechanisms of macroeconomic dialogue and cooperation put in place at different times to guarantee the consistency of the macroeconomic policies of major economies. These mechanisms have operated sometimes within the International Monetary Fund, but generally outside its institutional framework, and in recent years through the Group of Twenty. Finally, it analyses the functioning of the original Bretton Woods exchange rate system and its replacement in the early 1970s by a veritable 'non-system'.
Keywords: F32; F33; F42; 330; global imbalances; macroeconomic policy co-ordination; exchange rate system; International Monetary Fund; Group of Twenty